5 SIGLEC-7 IS HIGHLY AND SIMILARLY EXPRESSED ON TH1 AND TH2 LYMPHOCYTES. (1st March 2006) - Beerelli, P.; Meyers, S. B.; Mitchell, L. M.; Ghimbovschi, S. D.; Hoffman, E. P.; Freishtat, R. J.
Abstract : Purpose: Siglec-7 is an NK-receptor that negatively regulates cell activation via its intracellular tyrosine-based inhibitory motif (ITIM) when bound to its ligands, sialic acid-containing glycans of glycoproteins and glycolipids. Recent reports identified Siglec-7 on T cells and showed that it is capable of negative regulation of TCR signaling. As part of a larger study identifying novel differentiating markers between TH1 and TH2 lymphocytes in respiratory illness, we aimed to determine whether Siglec-7 is differentially expressed between TH1 and TH2 lymphocytes. Methods: A novel antibody cocktail was used to negatively enrich TH1 and TH2 cells from the PBMCs of healthy volunteers. Microarrays allowed determination of differential gene expression. RT-PCR was performed for selected targets. Protein markers were studied using flow cytometry before and after activation. Results: Isolates were > 95% pure TH cells with enriched TH1 (90.3%) and TH2 (84.1%) subsets. Expression profiling showed differential expression of Siglec-7 mRNA between TH1 and TH2 cells (TH1:TH2 ratio = 3.1). RT-PCR showed lower expression of Siglec-7 in TH1 cells (TH1:TH2 = 0.64 ± 0.06). Flow studies of resting and activated TH1 and TH2 lymphocytes showed increased expression of Siglec-7 from (mean ± SEM) 59.7 ± 16.5% of cells (mean fluorescence intensity = 24.1 ± 3) to 43.4 ± 24% of cells (19.3 ± 4.5) ( p = NS) for TH1 cells and from 70.4 ± 13.3% of cells (48.3 ± 5.6) to 48.2 ± 24.5% of cells (29.6 ± 3.2) ( p = NS) for TH2 cells. Conclusions: We found marked expression levels of Siglec-7 on both quiescent and activated TH1 and TH2 fractions. The abundance of this receptor suggests that it may play an important role in regulating TH cell activation as it does on NK cells. This also implies that there may be value in examining the role of TH cell Siglec-7 in the immune response to influenza A and B, which express neuraminidase, a sialidase that cleaves sialic acid from glycoproteins.